An Effective Adaptive Computed Torque PID Controller for Robotic Manipulators - Vo, Nguyên Thông; Nguyen, Hải Phong; Nguyen, Đặng Hùng Phú; Dang, Sỹ Bình; Dang, Xuân Ba (Journal of Technical Education Science, 2022)
Precise control of industrial manipulators has always been the primary research goal of robotics companies as well as academics. However, uncertainties in the system kinematics/dynamic models and unpredictable internal and external disturbances that arise as the systems operate are major barriers to access outstanding controllers. In this paper, we introduce an adaptive controller based on the computed-torque control structure for robotic manipulators. First, uncertain parameters such as load, link mass, and coefficients of friction, which appear in the nonlinear dynamics model of the robot, are estimated online and used in a model-compensation signal. To ensure convergence of both the main control error and the adaptive process, a proportional-integral-derivative (PID) control signal is used. Stability of the closed system and the convergence of the estimated parameters as well as the effectiveness of the controller were intensively investigated both by theoretical proof and simulation validation.